Ablation Versus Amiodarone for Treatment of Persistent Atrial Fibrillation in Patients With Congestive Heart Failure and an Implanted Device: Results From the AATAC Multicenter Randomized Trial. Issue 17 (26th April 2016) - Di Biase, Luigi; Mohanty, Prasant; Mohanty, Sanghamitra; Santangeli, Pasquale; Trivedi, Chintan; Lakkireddy, Dhanunjaya; Reddy, Madhu; Jais, Pierre; Themistoclakis, Sakis; Dello Russo, Antonio; Casella, Michela; Pelargonio, Gemma; et al.
Abstract : Background—: Whether catheter ablation (CA) is superior to amiodarone (AMIO) for the treatment of persistent atrial fibrillation (AF) in patients with heart failure is unknown. Methods and Results—: This was an open-label, randomized, parallel-group, multicenter study. Patients with persistent AF, dual-chamber implantable cardioverter defibrillator or cardiac resynchronization therapy defibrillator, New York Heart Association II to III, and left ventricular ejection fraction <40% within the past 6 months were randomly assigned (1:1 ratio) to undergo CA for AF (group 1, n=102) or receive AMIO (group 2, n=101). Recurrence of AF was the primary end point. All-cause mortality and unplanned hospitalization were the secondary end points. Patients were followed up for a minimum of 24 months. At the end of follow-up, 71 (70%; 95% confidence interval, 60%–78%) patients in group 1 were recurrence free after an average of 1.4±0.6 procedures in comparison with 34 (34%; 95% confidence interval, 25%–44%) in group 2 (log-rank P <0.001). The success rate of CA in the different centers after a single procedure ranged from 29% to 61%. After adjusting for covariates in the multivariable model, AMIO therapy was found to be significantly more likely to fail (hazard ratio, 2.5; 95% confidence interval, 1.5–4.3; P <0.001) than CA. Over the 2-year follow-up, the unplanned hospitalization rate was (32 [31%] in group 1 and 58 [57%] in group 2; P <0.001), showing 45% relative risk reduction (relative risk, 0.55; 95% confidence interval, 0.39–0.76). A significantly lower mortality was observed in CA (8 [8%] versus AMIO (18 [18%]; P =0.037). Conclusions—: This multicenter randomized study shows that CA of AF is superior to AMIO in achieving freedom from AF at long-term follow-up and reducing unplanned hospitalization and mortality in patients with heart failure and persistent AF. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00729911.